Self-directing skills, metacognitive beliefs, learning styles and exam anxiety in state high school students - Hariri, Seyyed Ali; Seadatee Shamir, Aboutaleb (International Journal of Education and Cognitive Sciences, 2022)
The aim of the current study was to investigate the relationship between self-directed skills, Meta cognitive beliefs and learning styles with exam anxiety. The present study is qualitative and co relational study and from goal view was fundamental study. Statistical studies population was consist of all state high school Bojnourd student in academic year of 93-94. 331 participants have been selected through Kerjeci and Morgan formula and by employing multistage cluster sampling. Self-directed skills, Meta cognitive beliefs, learning styles questionnaire with exam anxiety scale were employed for the assessment of the variables. Statistical Finding by using structural educational modeling and confirmatory factor analysis reveals that only three relations (effect) among all effect of the model were significant. Self-directedness had direct and positive effect on learning styles. Meta cognitive beliefs had direct and negative effect on exam anxiety. Also learning styles had direct negative effect on exam anxiety. Increasing self-directed skills leads to increasing the quality of Meta cognitive beliefs. However, as different factors were affecting exam anxiety self-directed skills cannot have significant influence on exam anxiety of students. Although Meta cognitive beliefs had direct significant influence on exam anxiety of students but by mediation of learning style this relationship turns to be no significant. Because Meta cognitive beliefs by mediation of learning style cannot prevent forgetting format students learning and destroying students function on exam context.